2011
DOI: 10.1007/s12571-011-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Harmonizing agriculture and health sector actions to improve household nutrition: policy experiences from Afghanistan (2002–2007)

Abstract: Coordination across sectors to address undernutrition with its varied underlying causes remains a challenge in developing countries. In Afghanistan, harmonization of health and agriculture policies and actions to reduce endemic undernutrition occurred during 2002-2007. This qualitative case study explores the forms of harmonization, enabling features and constraints in the policy process. We interviewed 57 stakeholders (39 central level, 18 provincial) involved in public nutrition or food security issues. Form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Another consistent finding in the literature is that NANs are more likely to be cohesive in the presence of leaders capable of managing complex relationships, conflicts, and competing interests among members, while increased cohesion can in‐turn reinforce the strength of leadership . Nutrition leaders enhance the strategic capacities (ie, “soft‐power” skills) of NANs and are thereby more capable of building internal cohesion and managing external commitment‐building activities across multiple sectors and levels . This resonates with the findings of a recent four‐country Sub‐Saharan Africa study that “boundary‐spanning actors” intentionally engaged in boundary‐spanning actions (eg, brokering, conflict resolution, coordinating, convening, diplomacy, framing, networking, and negotiating) are a feasible and acceptable approach to fostering policy action within complex multisectoral and multiagency nutrition governance contexts .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Another consistent finding in the literature is that NANs are more likely to be cohesive in the presence of leaders capable of managing complex relationships, conflicts, and competing interests among members, while increased cohesion can in‐turn reinforce the strength of leadership . Nutrition leaders enhance the strategic capacities (ie, “soft‐power” skills) of NANs and are thereby more capable of building internal cohesion and managing external commitment‐building activities across multiple sectors and levels . This resonates with the findings of a recent four‐country Sub‐Saharan Africa study that “boundary‐spanning actors” intentionally engaged in boundary‐spanning actions (eg, brokering, conflict resolution, coordinating, convening, diplomacy, framing, networking, and negotiating) are a feasible and acceptable approach to fostering policy action within complex multisectoral and multiagency nutrition governance contexts .…”
Section: Resultssupporting
confidence: 77%
“…Consistent with the framework of Shiffman et al, an expansion in the number and diversity of members may enhance the strategic expertise and organizational capacities and resources available to NANs, although it may also increase the potential for conflict and fragmentation . Greater capacities may in‐turn support the production of robust data and evidence, thereby supporting actions to develop a unifying discourse and hence greater cohesion . The expansion of donor or government nutrition budgetary commitments, adequate funding, and effective financing have enabled many NAN activities .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Ten years ago, Johnecheck and Holland (2007) envisaged a multisectoral approach to improving malnutrition in Afghanistan, while various other research outcomes have identified gaps between the agricultural and nutrition sectors, and highlighted the significance of food-based approaches to improving nutrition (Levitt, Pelletier and Pell 2009a;Levitt et al 2009b;Levitt et al 2010;Levitt et al 2011). Nevertheless, current policies do not emphasise the role of agriculture and food-based strategies for improving nutrition.…”
Section: The Afghan Contextmentioning
confidence: 99%
“…In a comparison of stakeholder priorities and perceptions of malnutrition in Afghanistan, Levitt et al (2009) found that agriculture and health sector stakeholders differed consistently in problem definition. Consensus-building using a shared causal framework, strategic alliances, and policy entrepreneurs with operational and strategic capacity were factors that allowed the policy process to proceed more successfully (Levitt et al 2011). …”
Section: Introductionmentioning
confidence: 99%